Does Democracy Entail an Obligation to Make Rational Policy Decisions? The Muddling Through vs. Bounded Rationality Debate Through a Lockean and Madisonian Lens. (3rd July 2020) - Reed, Ryan; Curtis, Craig; Lovrich, Nicholas P.
Abstract : The election of Donald Trump in 2016 has renewed concerns about nonrational decision making in American government. One view of the decision-making process, bounded rationality, is that decisions by managers in public agencies must be based on rational attempts to achieve policy goals. In opposition, advocates of successive limited comparisons argue that rationality, so conceived, is too often impossible to achieve in practice, and that better results can be attained through muddling through. Those who do not trust "technocrats" to make policy decisions would prefer that they be made with more political input than would be provided under an attempt to approximate rationality. This article offers an argument that in order to serve the public interest as envisioned by the designers of our institutions, American democracy mandates that public organizations base their policy decisions on a rational analysis of causal relations between the policy and the underlying behavior that is the object of the policy. This argument is based on reflections on the foundational writings of John Locke and James Madison advancing the use of reason to manage inevitable conflict in democratic societies and, in so doing, to achieve the public good.